Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1046/j.1469-0705.1996.07060443.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography vs. hysteroscopy in the preoperative staging of endometrial carcinoma

Abstract: The aim of this study was to evaluate the diagnostic accuracy of transvaginal sonography vs. hysteroscopy in the preoperative staging of endometrial carcinoma, in order to establish the most appropriate surgical therapy. Transvaginal sonography and hysteroscopy were used preoperatively in 67 women with histologically proven endometrial carcinoma. Deep myometrial invasion (> 50%) was present at postoperative pathology in 26/67 (39%) women and spread to the cervix occurred in 11/67 (16%) women. Transvaginal sono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
27
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 0 publications
7
27
0
2
Order By: Relevance
“…Our results were similar to those of earlier studies: sensitivity was 79% and NPV 86% with a lower specificity (72%) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) . In contrast with the other studies, ours was performed in several clinics as part of the routine workup by sonographers or gynecologists.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were similar to those of earlier studies: sensitivity was 79% and NPV 86% with a lower specificity (72%) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) . In contrast with the other studies, ours was performed in several clinics as part of the routine workup by sonographers or gynecologists.…”
Section: Discussionsupporting
confidence: 92%
“…Transvaginal sonography (TVS) has been used during the past few years to preoperatively determine the myometrial infiltration of endometrial cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) . The present study was undertaken to evaluate preoperative TVS for myometrial invasion assessment in daily practice in various university and nonuniversity hospitals.…”
mentioning
confidence: 99%
“…Analyzed separately, our results regarding TVS are similar to those of previous studies [16][17][18]25,33,34 , showing a high sensitivity and specificity. We had two cases of overestimation of myometrial invasion.…”
Section: Discussionsupporting
confidence: 89%
“…Magnetic resonance imaging (MRI) has been demonstrated to be highly accurate, with sensitivity ranging from 56 to 91% [29][30][31][32] . TVS has also been found to be accurate, with sensitivity ranging from 78 to 93% [16][17][18]25,33,34 . Some studies have demonstrated that TVS is as accurate as MRI 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study we have compared the diagnostic performance of TVS and CA 125 in detecting myometrial invasion in patients with endometrial cancer. Analyzed separately, our results regarding TVS are similar to those of previous studies [16][17][18]25,33,34 , showing a high sensitivity and specificity. We had two cases of overestimation of myometrial invasion.…”
Section: Discussionsupporting
confidence: 89%